A STUDY ON THE CORRELATION BETWEEN PERSONALITY AND SPEAKING PROFICIENCY OF THE FIRST SEMESTER ENGLISH LITERATURE STUDENTS OF FIB UB 2012 - RAHMAN, MUHAMAD ABDUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: personality, speaking proficiency, the first semester English literaturestudents of FIB UB 2012. In speaking learning process, students will be asked to communicate individually or in a group to make the audiences can understand what speaker mean well. How to speak can show personality. There are expressive and critical aspects in speaking. In addition, there are also calm and clear speaking. There are strength and weakness in each speaking. Students sometimes speak critically tends to be thinker, introvert, and pessimistic. Meanwhile, students who speak slowly tend to be kind, balanced emotion, and easy to deal. From the explanation, researcher is interested in analyzing about personality profile and the correlation personality with speaking proficiency.The first year of English Literature students are as data source, meanwhile, questionnaire result adapted from Personality Plus (1992) is as data research. Thisresearch uses correlational quantitative approach.There are 63 students as samples which have speaking score. Speaking score is taken from Basic Oral and Auditory Skill lesson which trains students to speak English in the class. Here are the last scores, 34 students get A; 17 students get B+; 8 students get C+; and one student get C. There is no students who get D and E. At last, the result of the research is Melancholic and Sanguine personality are often used by the students, then, Phlegmatic and Choleric personality are in the medium range, sometimes. (rmelancholic choleric = 3,63; rsanguine= 3,50; rphlegmatic = 3,43; rcholeric = 3,33) In the correlation test using SPSS 16, the result is not found significant correlation (p>0,05) between personality and speaking proficiency with scores in each personality psanguine = 0,124; pcholeric = 0,321; pmelancholic = 0,081 and pphlegmatic = 0,900 so that H0 is accepted or there is no any correlation betweentwo variables because speaking scores can be taken from other factors such as,total  attendance, students’ behavior, and discipline in one semester.Researcher concludes that Melancholic and Sanguine are more usually used by the students than Phlegmatic and Choleric, and there is no any relation between personality and English speaking proficiency. Researcher also advises the next researcher to use qualitative approach by using 4-8 samples, students having each dominant personality so that the effectiveness of each personality can be detected.